Determination of Mercury In Biological Sample In Muar River Estuary - Rahman, Md. Mokhlesur; Yunus, Kamaruzzaman (2012)
This study was carried out at the Muar River Estuary, Johore, Malaysia. Biological samples biota namely Crassostrea irredalei, Perna viridis and Anadara granosa were collected during the monsoon season in November 2005. These samples were dried and boiled in acid solution for analysis. Cold Vapor Atomic Absorption Spectrometer (CV-AAS) was used for determining the mercury concentration in the collected samples. The average mercury concentration in Crassostrea irredalei, Perna viridis and Anadara granosa were 1.854 ± 1.012 µg g -1, 0.336 ± 1.125µg g -1 and 1.178 ± 1.182 µg g -1 respectively. These results reveal that biota especially Crassostrea irredalei and Anadara granosa are not safe to be taken due to the total mercury concentration exceeding 0.5 µg g -1 according to WHO.